Laser confers less embryo exposure than acid tyrode for embryo biopsy in preimplantation genetic diagnosis cycles: a randomized study - Valle Marcelo; Lisboa Cintia B; Bossi Renata; Geber Selmo; Sampaio Marcos (BMC, 2011)
Abstract We compared two methods of zona pellucida drilling. 213 embryos were biopsied with acid Tyrode. Each biopsy took 3 minutes and the entire procedure ~29 minutes. 5% of blastomeres lysed, 49% of embryos became blastocyst and 36% of patients became pregnant. 229 embryos were biopsied with laser. Each biopsy took 30 seconds and the entire procedure ~7 minutes. 2.5% of blastomeres lysed, 50.6% of embryos became blastocyst and 47% of patients became pregnant. We can conclude that laser can be used for embryo biopsy. Reduction of embryo exposure and of removed blastomeres is associated with increased blastocysts available for transfer and a better clinical outcome.